Upaya Menumbuhkan Budi Pekerti Melalui Pendidikan Sains Berbasis Kearifan Lokal - Eryuni Ramdhayani; Wiwi Noviati (Indonesian Publication Center, 2020)
This research is backgrounded by Indonesia's global problem of mental crisis in all dimensions. This is indicated by the number of cases that occur such as to moral irregularities and behaviors that are not appropriate to norms such as juvenile delinquency, increased criminality, the cultural practice of KKN, interethnic conflicts, religions, politicians, and decreased work ethic, etc. The purpose of this research is to examine how to cultivate character through science education based on local wisdom, and the integration of character values in science education based on local wisdom. The research method used is the literature review that refers to library sources such as books, articles, journals, records, and electronic media that are relevant to the problems of the research. The result of this research is that the character can be grown through science education based on local wisdom with a method of exemplary or modeling.